Determinants of Generation Z Consumtive Behavior - Merliyana, Reny Dany; Syakinah, Fitri (Fakultas Ekonomi Universitas Garut, 2024)
Â This research on the consumptive behavior of Generation Z began with the author's interest in their financial management, especially students. The author wants to know how the understanding of financial literacy, the amount of pocket money, and the high lifestyle can affect the consumptive behavior of Generation Z. This research is urgent, because to find out the behavior of Generation Z in managing their finances and provide a good understanding through research results, so that they become wiser in managing their finances, do not behave consumptively and are motivated to save.Â The author uses quantitative data through questionnaires on 254 respondents, using data analysis techniques tested with SPSS 29 software. The final result of the study is that Financial Literacy and Lifestyle have a positive and significant influence on Consumptive Behavior, while Pocket Money has no effect and is negatively correlated with Consumptive Behavior.